The two Taríacuris and the Early Colonial and Prehispanic past of Michoacán - Haskell, David L., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
Investigates how elites of the Tarascan kingdom of Central Mexico sought to influence interactions with Spanish colonialism by reworking the past. Examines the rhetorical power of the Relación de Michoacán--by Franciscan friar Jerónimo de Alcalá and explaining the structure of the narrative, not just its content.--Provided by publisher.
Introduction: the two Taríacuris -- The Tarascan kingdom and its prehispanic past in Mesoamerican context -- The methodological and theoretical background to the analysis of the Priest's Speech: historicity and narrative structure -- Analysis of the Priest's Speech in the Relación de Michoacán -- Tarascan historicity in and through the priest's speech in the Relación de Michoacán -- Tarascan historicity in its Mesoamerican context: myth, history, historicity, and understanding the prehispanic past.
Keywords: Relación de Michoacán -- Criticism, Textual; Tarasco Indians -- Social life and customs; Tarasco Indians -- History -- Sources; Indians of Mexico -- Mexico -- Michoacán de Ocampo -- History -- Sources; Michoacán de Ocampo (Mexico) -- History -- Sources